(3cJGH GdCNjGQs ((3ESeGYjd Hf HcQ Hf YeQ s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdMeO ddg QH GdYGdejf hGdYGbHI ddeJbjf CeG HYO aGYde Cf GSe gPG GdcJGH cJGH GdCNHGQ hHfGDg Ydi CQHYjf HGHkG hai cd HGH YTQI CMGOjK s
(3BNQgG (B:s
(3bGd CHh SYjO GdNOQi QVi Gddg Yfg CNdGb SjO GdHTQcGf jYda GdHYjQ hGdOhGH hcGf Wdb GdhLg ef ZjQ YHhS eJhGVYkG ef ZjQ OdI hde jeO jOg Edi WeY JeJ GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
Keywords: (3GdMOjK h GdeUWdMs